Optimal and robust design of materials for wind turbine - Rashedi A M Mabrur Ahmad (2014)
The world today is continuously striving towards carbon neutral clean energy technology. Hence, renewables like wind power systems are increasingly receiving the attention of mankind. Energy production is now no more the sole criterion to be considered when installing new megawatt (MW) range of turbines. Rather some important design parameters like material choice, cost, carbon footprint, embodied energy, life cycle impact efficiency and, above all, the structural rigidity needs to be considered holistically. Accordingly, these issues are followed up in this dissertation from the wind industry perspective. The study, at the outset, performs a detailed life cycle assessment (LCA) of three wind farms to explore long term impacts of today’s MW range wind turbines. Out of these, the vertical axis wind farm performs the best; followed by offshore horizontal axis and onshore horizontal axis farm. Corresponding studies consequently discover most adverse life cycle impact contributing materials and subsequently replace them with superior ones which eventually reduce overall LCA impacts by 30%, 25%, 7% for modified HAWT onshore, HAWT offshore and vertical axis farm, respectively. Eventually, a comparison of all major renewable and non-renewable power generation sources reveal the wind farms as competing remarkably with all the technologies except the hydro-kinetic ones. Next, the study aims to distinguish best blade and tower materials in comparison to presently used ones in line with multiple constraint and compound objective based design optimization principle whereby mass, carbon footprint, material cost and embodied energy minimization are achieved simultaneously from material indices derived of aerodynamic and structural performance equations. In this way, final onshore wind turbine blade material ensures 74% mass, 17% carbon footprint, 30% embodied energy reduction in comparison to existing Vestas 3.0 MW glass/epoxy blade. In turn, a cast iron BS 900/2 material tower ensures 6% mass, 81% carbon, 80% energy content and 90% cost reduction in comparison to present tower material. Natural composite materials like oak, lignumvitae also enter into small scale onshore blade design space for low wind regions. Composite materials appear as one of the most potential material families from both material indexing and life cycle assessment study. Hence, the study is extended on how to ensure material efficiency in composite structure through fracture characterization under experimental biaxial loading. Owing to their anisotropic nature, composite materials respond differently under multi-axial loading conditions with reference to their uniaxial behavior and, hence, characterization of its multi-axial stress properties is of utmost importance for wide scale, efficient usage in numerous structures including wind turbine blades. A new biaxial test frame is developed, relevant optimized geometry is achieved, relevant geometric factors corresponding to cruciform profile is determined and, based on these, glass fibre composite material is characterized for its fracture performance with different crack dimensions and orientations. Under biaxial tensile-tensile loading condition, composite material is able to sustain more load than uniaxial case which opens the door for less conservative design and increased material efficiency. A companion study is performed in pursuit of a mass minimal design for thin cylinder structure under eccentric compressive loading, as a representative form of wind turbine tower. In this concourse, axial crushing failure is studied first under non-uniformly distributed loading. Next, leading compressive failure modes such as global buckling, yield, local buckling are studied with respect to non-dimensional load and shape factor. Optimal failure boundary zones are attained simultaneously with minimal mass and optimum shape factor based design perspective. Final failure boundary plot serves as a design tool for wind turbine tower where eccentric compression is one of the loading conditions. Findings from these studies can be deployed to harness massive scale wind energy from structurally more promising, economically more competitive and environmentally more clean and green turbine.